Clinical and laboratory findings of hookworms (Ancylostoma spp.) in naturally infected adult dogs - Santos, Bruna dos [UNESP]; da Silva, Naiara Mirelly Marinho [UNESP]; Mora, Silvia Eugenia Vargas [UNESP]; Justo, André Augusto; Santos Schmidt, Elizabeth Moreira dos [UNESP]; Takahira, Regina Kiomi [UNESP] (Revista Brasileira de Medicina Veterinaria, 2024)
Intestinal parasites of the genus Ancylostoma are the most prevalent in coproparasitological examinations and necropsies of dogs in Brazil. Although adult dogs often remain asymptomatic when infected, there is limited published information concerning the laboratory and clinical findings and severity of infection in symptomatic adult dogs. Therefore, this study aimed to characterize the clinical and laboratory findings of adult Ancylostoma-infected dogs. Data were obtained by surveying the medical records of dogs treated at a University Veterinary Hospital from June 2009 to June 2019. Of 243 cases, 30 met the selection criteria. The most frequent clinical signs were diarrhea and hematochezia (13/30 each - 43.3%), and the most common laboratory findings were eosinophilia (13/30 - 43.3%), increased RDW (6/29 - 20.7%), and hypoalbuminemia (5/21 - 23.8%). Dogs with Ancylostoma spp. presented an increased proportion of high RDW (P= 0.010) compared with non-parasitized dogs. Dogs with higher fecal egg scores (n= 18) showed significantly lower RBC (6.26 ± 0.64 vs 7.24 ± 0.74 106/µL, P< 0.001) and albumin levels (2.8 ± 0.5 vs 3.2 ± 0.4 g/dL, P= 0.021), and an increased eosinophil count (1.42 ± 0.95 vs 0.58 ± 0.47 103/µL, P= 0.003) compared with the control group. Fecal egg scores exhibited a weak correlation with eosinophils (r = 0.42, P= 0.002) and a moderate correlation with RBC (r = -0.52, P< 0.001). In conclusion, despite relevant clinical signs, the laboratory findings were indicative of mild alterations in adult dogs, especially in those with lower scores of eggs in coproparasitological tests.
Achados clínicos e laboratoriais da ancilostomíase em cães adultos naturalmente infectados
Keywords: ancylostomiasis; canine; complete blood count; RDW; serum biochemistry